Nadir aaj kia pehnay - Maryam, Shera; Shireen, Syed (book group Karachi, 1998)
Nadir Aaj Kya Pehnay (What Should Nadir Wear Today?) is likely a children's story in Urdu that revolves around the dilemma of choosing an outfit for the day. The story might involve Nadir trying on different clothes, seeking advice from family members, and ultimately making a decision about what to wear. It could highlight the importance of dressing appropriately for different occasions and personal style.